Drag Reduction in Compressible Channel Turbulence with Periodic Interval Blowing and Suction - Shibo Lee; Chenglin Zhou; Yang Zhang; Yunlong Zhao; Jiaqi Luo; Yao Zheng (Applied Sciences, 2025)
This paper employs direct numerical simulation (DNS) to investigate the influence of blowing and suction control on the compressible fully developed turbulent flow within an infinitely long channel. The spanwise blowing strips are positioned at uniform intervals along the bottom wall of the channel, while the suction strips are symmetrically placed on the top wall. The basic flow (uncontrolled case) and the controlled cases involving global control and interval control are compared at <semantics>Ma=0.8</semantics> and 1.5. Although the wall mass flow rate remains constant across all controlled cases, the applied blowing/suction intensity and spanwise strip areas exhibit significant variations. The numerical results indicate that augmenting the blowing/suction intensity will alter the velocity gradient of the viscous sublayer in the controlled region. Nonetheless, a reduction in the area of the controlled region diminishes the impact of blowing/suction on drag reduction on the entire wall. The spatially averaged velocity profiles on the wall for cases with identical wall mass flow rates are nearly indistinguishable, suggesting that the wall mass flow rate is the primary factor influencing the spatially averaged drag reduction rate on the entire wall, rather than the blowing/suction intensity or the injected energy. This is because the wall mass flow rate influences the average peak position of the Reynolds stress, which, in turn, affects the skin friction drag. An increase in the wall mass flow rate correlates with a heightened drag reduction rate on the blowing side, while simultaneously leading to a rising drag increase rate on the suction side.